NĀZIK AL-MALĀ`IKAH: Sepintas Biografi dan Pemikirannya tentang Puisi Bebas (Studi Tokoh Sastra Arab) - Achmad Atho`illah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
This article aims to provide a short biography of Iraqi Arab poet, Nāzik al-Malā`ikah, and her thoughts about free verse (al-syi’r al-h} urr). In this paper, the writer applies her personal life history. The results of this article show that Nāzik is a popular figure in modern Arabic literature. She occupies a prominent position not only because of her innovative experimental poetry, but also because of her critical theories. Since the publication of her first collection, ‘Āsyiqah al-Lail (1947),—which contains one of her best known works entitledKūlīra—she has contributed toward transforming Arabic poetry in terms of its orientation and structure. This is reflected equally in her works and in her critical theorization of the new poetic form known as free verse (al-syi’r al-h} urr). In 1949, she published her second volume of poems, Syazāyā wa Ramād, and prefaced it with a theory of new poetry metrics. Nāzik defines free verse (alsyi’r al-hurr) as any poetry that departs from the twohemistich line system and that employs the taf'ilah “foot”. And, the basic of the taf'ilah poetry is the unity of metrical foot. In her theory of new poetry metrics, she recommended two kinds of meters. They are pure meters (al-buhūr al-sāfiyah) and mixed meters (al-buhūr al-mamzūjah).